Effect of Persian and almond gums as fat replacers on the physicochemical, rheological, and microstructural attributes of low‐fat Iranian White cheese - Jooyandeh, Hossein (Food Sci Nutr, 2016)
The effect of Persian and almond gums (0, 0.1 and 0.2% (w/w)) as fat replacers and milk fat (0.4, 0.9, and 1.4% (w/w)) on physicochemical and rheological characteristics and microstructure of low‐fat Iranian White cheese was studied. Persian and almond gums both effectively increased moisture‐to‐protein (M:P) ratio of low‐fat cheese samples which in turn led to a significant reduction in the hardness parameters fracture stress and Young's and storage (G’) moduli (p < .05); however, the effect of Persian gum was more pronounced (p < .01). Gum addition promoted cheese yield and proteolysis rate (p < .05). Response surface optimization described that supplementation of cheese milk containing 0.9% fat with 0.2% Persian gum and 0.12% almond gum would result in a low‐fat cheese with textural properties similar to its full‐fat counterpart. Scanning electron microscopy revealed that the fat replacers produced full‐fat‐like structure in the low‐fat Iranian White cheese, when incorporated at the optimum levels.